Eternal Now: Recent Time Loop Movies and the Sanctity of the Moment - Lyden, John (The journal of religion and film, 2018)
I will examine three time-loop films - Source Code (2011), About Time (2013), and Before I Fall (2017) - to suggest that while they all look to this world as the place where meaning can be found, they do not entirely reject transcendence. The hero of Source Code actually transcends the cycle only when he accepts to exist in it fully, suggesting a view like Buddhism that one only finds transcendence when one stops looking for it. In About Time the hero learns that he must accept certain things that he cannot change, and that his ability to relive the past without changing anything is actually the key to happiness and meaning. In Before I Fall, the heroine returns her to the day before her death repeatedly to work out her own salvation through redemptive action. In different ways, each film suggests how meaning can be found through an awareness of the eternal now.